Integrated metabolomic and transcriptomic analysis provides insights into the browning of walnut endocarps - Wang, Yifeng; Wang, Mingxia; Chen, Yaonian; Hu, Wenbin; Zhao, Shuling (Frontiers in Plant Science, 2025)
Walnut (Juglans regia L.) is an important woody plant worldwide, and endocarp color affects the economic value of walnut. During the postharvest processing and storage of walnut, the endocarp often undergoes browning. Browning has become a major obstacle to walnut storage, not only affecting the taste and flavor of walnuts but also reducing their nutritional quality and commercial value. In the present study, to elucidate the molecular mechanism of walnut endocarp browning, analyses of the ultrastructure, physiological characteristics, and transcriptomic and metabolomic data of walnut endocarps at different storage periods were performed. Integrated transcriptomic and metabolomic analysis showed that many differentially expressed genes (DEGs) and metabolites (DAMs) were involved in the pathways of flavonoid biosynthesis, amino acid biosynthesis, unsaturated fatty acid biosynthesis, phenylalanine metabolism, and oxidative phosphorylation. Among them, the expression levels of DEGs related to flavonoid metabolism and antioxidant activity had significant differences during their storage periods. In addition, the expression of stress-related transcription factors AP2/ERF, WRKY, bHLH, HSF, and MYB involved in the phenylpropanoid metabolic pathway was significantly upregulated during the browning process. This study comprehensively analyzed the causes of walnut endocarp browning, providing insights for studying the molecular mechanism of endocarp browning during storage and processing of walnuts and other fruits.